2023
DOI: 10.1007/s40123-023-00669-1
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease Associated with Meibomian Gland Dysfunction: Focus on Tear Film Characteristics and the Therapeutic Landscape

Abstract: Meibomian gland dysfunction (MGD) is highly prevalent and is the leading cause of evaporative dry eye disease (DED). MGD is characterized by a reduction in meibum secretion and/or a change in meibum composition that results in the disruption of the tear film lipid layer and an increase in the tear film evaporation rate. Excessive evaporation causes tear film instability, desiccation, tear hyperosmolarity, inflammation, and apoptosis of ocular surface cells, resulting in a continuous cycle of DED. The primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 161 publications
0
12
0
Order By: Relevance
“…DED remains a considerable public health concern, which affects a large portion of the global population . There are currently no curing treatments on the market for DED and leading ophthalmologists have proclaimed that there is an immediate demand for new types of DED-treatments that successfully target the tear film instability and excessive tear evaporation defects caused by the disorder . In this work, we set out to develop a new treatment strategy that is capable of targeting the main defects caused by DED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DED remains a considerable public health concern, which affects a large portion of the global population . There are currently no curing treatments on the market for DED and leading ophthalmologists have proclaimed that there is an immediate demand for new types of DED-treatments that successfully target the tear film instability and excessive tear evaporation defects caused by the disorder . In this work, we set out to develop a new treatment strategy that is capable of targeting the main defects caused by DED.…”
Section: Discussionmentioning
confidence: 99%
“…While aqueous ocular lubricants are the most widely used treatments, they are unable to successfully target the tear film instability and excessive tear evaporation defect (present in >80% of DED-cases). Thus, they offer only a brief alleviation of symptoms even upon frequent application. Anti-inflammatory agents, on the other hand, are associated with several adverse effects (e.g., ocular hypertension and cataracts) in long-term use, which poses a challenge when the chronic nature of some instances of DED is considered. Therefore, the expert ophthalmologists have called for the immediate development of improved DED treatments capable of successfully targeting the tear film instability and excessive tear evaporation defects associated with the disease . Within the scientific community, there is a growing consensus that strategies focusing on the tear film lipid layer (TFLL) hold significant potential for improving the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that blink videos with 30 FPS have higher accuracy in detecting incomplete blinking which was a sensitive indicator of DED [ 59 ]. Another important predictive factor of DED is meibomian gland dysfunction (MGD) which results in the disruption of the tear film lipid layer and increases the tear film evaporation rate [ 60 ]. A mask region based convolutional neural network (RCNN) algorithm has been explored in achieving automatic identification of MGD by applying it on analyses of 1878 non-invasive infrared meibography images [ 61 ].…”
Section: Main Textmentioning
confidence: 99%
“…Tear proteins can be classified according to their abundance. 3 The bulk of the tear protein concentration is made up of a few high abundance lacrimal proteins (mg/mL to mg/mL): lysozyme, lipocalin, lactoferrin, secretory immunoglobulin A (IgA), plasma-derived albumin, and lipophilin. 4,5 Proteins secreted by the ocular tissue or cell signaling molecules tend to be of moderate abundance (mg/mL to ng/mL) and cytokines and growth factors in low abundance (ng/mL to pg/ mL).…”
mentioning
confidence: 99%